Formation of the Jurassic Changboshan‐Xieniqishan highly fractionated I‐type granites, northeastern China: implication for the partial melting of juvenile crust induced by asthenospheric mantle upwelling. (17th October 2013) - Zhang, Daohan; Wei, Junhao; Fu, Lebing; Chen, Huayong; Tan, Jun; Li, Yanjun; Shi, Wenjie; Tian, Ning
Abstract Zircon U–Pb ages, major and trace elements, and Sr, Nd and Hf isotope compositions of the Changboshan‐Xieniqishan (CX) intrusion from the Great Xing'an Range (GXAR), northeastern China, were studied to investigate its derivation, evolution and geodynamic significance. Laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) zircon U–Pb dating yields an emplacement age of 161 ± 2 Ma for the CX intrusion. Bulk‐rock analyses show that this intrusion is characterized by high SiO2, Na2O and K2O, but low MgO, CaO and P2O5. They are enriched in large‐ion lithophile elements and light rare earth elements, with marked Eu anomalies (mostly from 0.36 to 0.65), and depleted in heavy rare earth elements and high field strength elements. Most samples have relatively low (87Sr/86Sr)i values (0.70423–0.70457), with εNd(t) fluctuating between −0.4 and 2.3. The εHf(t) for zircons varies from 5.4 to 8.7. Sr–Nd isotope modelling results, in combination with young Nd and Hf model ages (760–986 and 549–728 Ma, respectively) and the presence of relict zircons, indicate that the CX intrusion may originate from the partial melting of juvenile crust, with minor contamination of recycled crustal components, and then underwent extensive fractional crystallization of K‐feldspar, plagioclase, biotite, sphene, apatite, zircon and allanite. Considering the widespread presence of granitoids with coeval volcanic rocks, we contend that the CX intrusion formed in an extensional environment related to the upwelling of asthenospheric mantle induced by the subduction of the Palaeo‐Pacific plate, rather than a lithospheric delamination model. Copyright © 2013 John Wiley & Sons, Ltd.